Treatment of corneal ectasia by implantation of an allogenic corneal lenticule - Li, Meiyan; Knorz, Michael C. (Journal of refractive surgery, 2018)
Journal of Refractive Surgery | PURPOSE:To describe a case in which post-LASIK corneal ectasia was treated using an allogeneic lenticule implanted into the recipient eye.METHODS:A 29-year-old man presented with bilateral ectasia 10 years after LASIK. Manifest refraction was −1.50 −3.25 × 15° in the right eye and −13.50 −6.00 × 10° in the left eye. Because of contact lens intolerance in the left eye, the authors decided to
Gesehen am 23.09.2020